The Application of Problem Based Learning Models with E-Learning during the Covid-19 Pandemic to Students’ Science Process Skills of Class XI IPA Students at SMA Santo Paulus Manokwari - Irmawati Patabang; Irfan Yusuf; Alberto Y.T Allo; Sri Wahyu Widyaningsih (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2020)
This study aims to measure the effect of the application of the E-learning PBL assisted learning model on the science process skills of students of class XI IPA SMA Santo Paulus Manokwari. The research subjects were 4 people consisting of 3 men and 1 woman. This research is an experimental research with the method used is pre-experimental design. The research data was in the form of students' pretest and posttest scores taken using multiple choice test techniques. Meanwhile, students' science process skills were taken using a process skills assessment sheet that was assessed by the observer. The average pretest and posttest scores of students were 42.97 and 70.50 whereas, for the results of KPS observations students had an average value of 73.61% of the six indicators assessed, where the indicator planning the experiment had the highest value, namely 79, 17 and the indicator with a low score is formulating a hypothesis, namely 66.67 and all of these indicators fall into the good category. This shows that there is an effect of the application of the PBL learning model on KPS students.